2001
DOI: 10.2337/diacare.24.8.1335
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Aggressive Versus Standard Lipid Lowering by Atorvastatin on Diabetic Dyslipidemia

Abstract: The DALI Study: a double-blind, randomized, placebo-controlled trial in patients with type 2 diabetes and diabetic dyslipidemia THE DIABETES ATORVASTATIN LIPID INTERVENTION (DALI) STUDY GROUPOBJECTIVE -In patients with type 2 diabetes, intensive glucose regulation, although effective for microangiopathy, has not been shown to have unambiguous preventive effects on the occurrence of cardiovascular disease. Patients with diabetes show a characteristic dyslipidemia (high triglyceride level, low HDL cholesterol le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…In a larger, placebo-controlled study of 217 dyslipidemic patients with type 2 diabetes mellitus, using polyacrylamide gradient gel electrophoresis, atorvastatin 10 mg and 80 mg significantly lowered LDL-C levels, significantly reduced apo B, and produced no significant effects upon LDL particle size. However, similar to this report, atorvastatin produced a numerical increase in the proportion of patients with Pattern B (21.3%, 21.4%, and 22.2% for placebo, atorvastatin 10 mg, and atorvastatin 80 mg, respectively)[27]. …”
Section: Discussionsupporting
confidence: 71%
“…In a larger, placebo-controlled study of 217 dyslipidemic patients with type 2 diabetes mellitus, using polyacrylamide gradient gel electrophoresis, atorvastatin 10 mg and 80 mg significantly lowered LDL-C levels, significantly reduced apo B, and produced no significant effects upon LDL particle size. However, similar to this report, atorvastatin produced a numerical increase in the proportion of patients with Pattern B (21.3%, 21.4%, and 22.2% for placebo, atorvastatin 10 mg, and atorvastatin 80 mg, respectively)[27]. …”
Section: Discussionsupporting
confidence: 71%
“…Meanwhile, antioxidant and anti-inflammation benefits of atorvastatin 80 mg were also observed in MIRACL and ASAP trails [38,39]. Besides, the aggressive (80 mg/d) and moderate (10 mg/d) lipid-lowering therapy with atorvastatin was compared in the DALI trail [40]. Consequently, Fasting TG was reduced by 35% with aggressive therapy and by 25% with moderate therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Carlsson et al86 conducted a study in a population with an incremented risk of AD (siblings of diagnosed patients) and found a slight improvement in some neuropsychological tasks (verbal fluency and working memory) but no effect on cerebrospinal fluid amyloid (42 fraction). Some additional small studies found some beneficial effects on cognition in statins users 9092. In the DALI study,90,92 a 24% improvement in a verbal memory test was observed in a group of diabetic patients treated with atorvastatin for 30 weeks.…”
Section: Statins and Admentioning
confidence: 98%